WOMEN RIGHTS FULFILLMENT AS THE VICTIM OF GROSS HUMAN RIGHTS VIOLATION: URGENCY FOR THE SEXUAL VIOLENCE ERADICATION BILL - Purwanti, Ani; Prabowo, Rian Adhivira (Indonesia Law Review, 2018)
Heretofore in Indonesia, cases of gross violation of human rights have faced an indefinite stagnation of justice. Although the Indonesian government has ratified international human rights conventions and enacted its own system of human rights law, such laws have proven unable to fulfill the restoration of justice toward these victims in two particular aspects: convictions against the perpetrators and reparations for the victims. This article focuses on fulfilling the rights of women victims of past gross human rights violations. It will be based on normative legal research by which the existing laws are critically analyzed in order to expose the legal gaps which might have contributed to the inability of these laws to restore justice and the victims’ well-being. Furthermore, the article stresses an urgency upon the enactment of the Sexual Violence Eradication Bill. It contends that the Sexual Violence Eradication Bill is an essential first step for the fulfillment of women victims’ rights, inasmuch as the bill includes an exhaustive mechanism of penal provisions against sexual crimes under various circumstances, including as part of gross human rights violations.